2012
DOI: 10.1002/art.34426
|View full text |Cite
|
Sign up to set email alerts
|

Association of noninvasively measured renal protein biomarkers with histologic features of lupus nephritis

Abstract: Objective To investigate the relationship of urinary biomarkers (UBM) and established measures of renal function (EMRF) to the histological findings with lupus nephritis (LN); and to test whether certain combinations of the above mentioned laboratory measures are diagnostic of specific histological features of LN. Methods Urine samples of 76 patients were collected within 2 months of a kidney biopsy and assayed for the UBM: lipocalin-like prostaglandin-D synthetase (LPGDS), α1-acid-glycoprotein (AAG), transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 50 publications
6
111
2
4
Order By: Relevance
“…Thus, investigations have recently evolved toward discovery and validation of lupus biomarker 'panels'. One approach in this regard has been technology-driven with the use of microarrays or proteomics for identifying novel gene or protein 'biosignatures' of SLE such as that discussed above for lupus nephritis [Brunner et al 2012]. Additional ongoing developments on this front are discussed briefly here.…”
Section: Sle Biomarker Panelsmentioning
confidence: 99%
“…Thus, investigations have recently evolved toward discovery and validation of lupus biomarker 'panels'. One approach in this regard has been technology-driven with the use of microarrays or proteomics for identifying novel gene or protein 'biosignatures' of SLE such as that discussed above for lupus nephritis [Brunner et al 2012]. Additional ongoing developments on this front are discussed briefly here.…”
Section: Sle Biomarker Panelsmentioning
confidence: 99%
“…Moreover, Cp is expressed by glomerular parietal epithelial cells and secreted into the urine in aging rats fed a high-calorie diet (25). Finally, Cp is also secreted into the urine in patients with early diabetic nephropathy (26), early IgA glomerulonephritis (27) and lupus nephritis (28). Cp may be a urinary biomarker in these diseases, and previous reports suggest that the antioxidant Cp expression in the kidney, mainly in Bowman's capsule, protects podocytes and downstream nephrons from the toxic effects of filtered molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, further longitudinal studies with larger sample size need to be conducted to confirm the clinical significance of urinary TWEAK as a novel biomarker that can reflect histological activity and determine treatment response. Brunner and colleagues reported that combinational analysis of anti-dsDNA antibody, serum C3, C4, creatinine, urinary protein creatinine ratio, and urinary biomarkers such as MCP-1, NGAL, lipocalin-type prostaglandin D-synthetase, α1-acid-glycoprotein, transferrin, and ceruloplasmin is useful in predicting activity, chronicity, and pathology of LN [18]. Therefore, it might be helpful to study the benefit of combining the urinary TWEAK and established biomarkers in LN patients.…”
Section: Is Urinary Tumor Necrosis Factor-like Weak Inducer Of Apoptomentioning
confidence: 99%